Evaluación de características de solución para tinturado sólido usando colorantes naturales en rosa (rosa sp.) variedad mundial, cantón Latacunga provincia Cotopaxi 2017 - Taipicaña Comasanta, Clímaco Miguel (2017)
The present investigation was carried out in the Laigua neighborhood of Maldonado parish Aláquez Cantón Latacunga Province Cotopaxi, in the florist SANBEL FLOWERS, with the purpose of the subject Evaluation of characteristics of solution for solid dyeing using natural dyes in Rosa Variety Mondial, in which we determine the Better dye solution pH, dye dose, solution temperature and natural dye. The methodology followed was the collection of the flower in the field, with a cut-off of 2.5, then allowed to dehydrate for 2 hours At 4 hours and the dyeing was performed, then all the natural dyes were prepared with the specific dose and the respective extracts, to place the dye in glasses with the help of a mesh to prevent the stems from falling then proceeded at 8 Hours for the data collection, and proceeded to remove the flower from the dye to hydrate and then make bonches of 24 stems each, was left hi Drained for 2 hours and proceeded to place in the cold room at 3-4 ° C, and made its packing to perform the flight test, which lasted 4 days, then removed the flower for placement in the vases and the Data collection was performed on a daily basis. The characteristics (dyeing hours, vase days, physiopathies and color intensity) of the solution for solid dyeing were evaluated using natural dyes (beet extract, annatto, black and orange). Treatment as 48 treatments were occupied 192 buttons in one repetition, but since there are 2 replicates for their study in total 384 buttons were used in total. it was observed that the sources of variation of temperature, ph, dose and colorant present good results in the factors studied.